(untitled) (Konturen, 2015)
This is a sequel to an earlier paper (’Kierkegaard’s Ethicist’ Archiv 2006) in which I argued that J.G. Fichte (rather than Kant or Hegel or some amalgam) was the primary historical model for the ethical standpoint described in Kierkegaard’s Either/Or II. Here I offer some new support for that claim. In the first section I present some evidence for Fichte’s prominence in the landscape of philosophical ethics in the 1830s and ’40s in Germany and Denmark. I argue that Kierkegaard’s use of Fichte as a foil was not idiosyncratic, but was rather the obvious choice in the historical context. In the second section I describe some additional substantive and textual reasons for thinking Fichte was the figure looming largest in the background of Kierkegaard’s construction of the ethical standpoint in Either/Or.